An Uncommon Presentation of Hamman's Syndrome in an Adolescent With Acute Diabetic Ketoacidosis and Newly Diagnosed Type 1 Diabetes - Daliya George; Malini Rajandran; Habib Bhurawala; Gary M. Leong (Hindawi Limited, 2024)
Hamman's syndrome, a rare complication of diabetic ketoacidosis (DKA), is characterized by subcutaneous emphysema and spontaneous pneumomediastinum. This case report discusses the occurrence of Hamman's syndrome in an 11-year-old adolescent male newly diagnosed with type 1 diabetes mellitus (T1DM) and presenting with severe DKA. The patient exhibited symptoms typical of DKA, including polydipsia, polyuria, abdominal pain, and fatigue, alongside signs such as dehydration, Kussmaul breathing, and tachycardia. Following initial management with intravenous fluids and insulin infusion, he was transferred to a tertiary children's hospital for further care. Subsequently, on routine examination, he exhibited bilateral neck crepitus and a mediastinal crunching sound on auscultation, indicative of Hamman's syndrome. Conservative management led to symptom resolution, and the patient was discharged with follow-up arranged. This case highlights the importance of recognizing Hamman's syndrome as a potential complication of DKA in pediatric patients. Prompt diagnosis and management, along with differentiation from more severe conditions like Boerhaave's syndrome, are crucial for ensuring favorable outcomes. Further awareness and understanding of this rare syndrome are essential for optimal patient care and management.